2015
DOI: 10.3892/ol.2015.3917
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Pygopus 2 inhibits vascular mimicry in glioma U251 cells by suppressing the canonical Wnt signaling pathway

Abstract: Abstract. Gliomas are the most common type of malignant primary brain tumor, and the Wnt signaling pathway is associated with glioma malignancy. Pygopus protein plays an important role in developmental brain patterning, and has been identified to be a component of the Wnt signaling pathway. In the present study, the Pygopus 2 (Pygo2) protein was examined in 80 glioma tissue samples. Short hairpin (sh) RNA-Pygo2 was transfected into glioma U251 cells, and the cell proliferation, colony formation and bromodeoxyu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Similar to our finding, Nowicki et al [26] reported that inhibiting GSK-3 through lithium could reduce the motility of gliomas. Another study reported that inhibiting the expression of Pygo2 could decrease the proliferation, colony formation, and BrdU incorporation of gliomas by reducing cyclin D1, a downstream gene of the Wnt/β-catenin signaling pathway [27]. The conclusion was analogous to the findings by Zhang.…”
Section: Discussionsupporting
confidence: 62%
“…Similar to our finding, Nowicki et al [26] reported that inhibiting GSK-3 through lithium could reduce the motility of gliomas. Another study reported that inhibiting the expression of Pygo2 could decrease the proliferation, colony formation, and BrdU incorporation of gliomas by reducing cyclin D1, a downstream gene of the Wnt/β-catenin signaling pathway [27]. The conclusion was analogous to the findings by Zhang.…”
Section: Discussionsupporting
confidence: 62%
“…Several mechanisms are involved in VM, including those related to the capacity of aggressive tumor cells to resemble features of the ECs such as cell adhesion (52), migration (53), extracellular matrix remodeling (54), perfusion (50), and maturation of blood vessels (55). Moreover, CSCs promote VM by deregulating pathways involved in embryonic development, such as the transforming growth factor β (TGF-β) (5658), Wnt (59), Notch (60, 61), Nodal (6264), and the Hippo pathways (6567), among others. EMT also plays an important role in VM, and encompasses the pathways previously mentioned as well as transcription factors such as Twist1/2 (68), Snail/Slug (69), and ZEB1/2 (34).…”
Section: Mechanisms and Signaling Molecules Involved In Vm In Ovarianmentioning
confidence: 99%
“…The Wnt family members regulate EC differentiation and vascular development (112) and has been associated with VM. In glioma and colon cancer, the canonical Wnt/β-catenin pathway induced VM by increasing the expression of VEGFR-2 and VE-cadherin (59, 113). Interestingly, in ovarian cancer, the non-canonical Wnt signaling is implicated in VM formation.…”
Section: Mechanisms and Signaling Molecules Involved In Vm In Ovarianmentioning
confidence: 99%
“…Previous research has demonstrated that the deletion of Pygo2 delayed tumor onset in Wnt‐1 transgenic mice that spontaneously developed extensive mammary adenocarcinomas (Watanabe et al 2014). Suppression of Pygo2 expression inhibited ovarian, lung cancer cell and glioma cells proliferation (Liu et al 2013b; Wang et al 2016). The Pygo2 oncogenic potential was also evaluated by xenograft assays in immunodeficient mice both for wild and knockdown Pygo2 epithelial ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%